Evaluation of Definitive Antibiotic Therapy Effectiveness in Sepsis Patients at Tabanan Hospital, Indonesia - Luh Rai Maduretno Asvinigita; Ketut Tunas; Ida Ayu Alit Widhiartini; Agata Widatama; Rini Noviyani (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND : The study evaluated the use of definitive antibiotics and examined the association between the causative bacteria, resistance patterns, and antibiotic regimens with clinical outcomes in sepsis. AIMS :  To assess the suitability of definitive antibiotics in sepsis patients at Tabanan Hospital, focusing on the correlation between bacterial type, antibiotics, and resistance profiles with clinical outcomes, aiming to improve sepsis management and reduce antibiotic resistance. METHOD : The observational cross-sectional study analyzed data descriptively to evaluate antibiotic-pathogen compatibility retrospectively. Chi-square tests were used for bivariate analysis of mortality-related variables. Survival analysis employed the Kaplan-Meier method. RESULT : Among 112 sepsis patient records (Jan 2020 - Dec 2022), 62% received antibiotics based on bacterial sensitivity test contradiction to another 38% who were given inappropriately antibiotic. Empiric antibiotic treatment was associated with increased mortality (OR=4.379; CI 95% 1.274-15.052; P=0.022). Bacterial type and resistance status showed no significant association with mortality (OR=0.417; CI 95% 0.030-5.708; P=1.000 and OR=1.500; CI 95% 0.156-14.420; P=1.000, respectively). CONCLUSION : Definitive antibiotic use for sepsis patients at Tabanan Hospital was mostly appropriate, and the empiric antibiotics treatment was associated with mortality, while the causal bacteria and resistance status were not significantly associated with mortality.  Findings highlight the importance of transitioning from empiric to targeted therapy to potentially reduce mortality in sepsis management.